Microstructure investigations and thermoelectrical properties of an N-type magnesium–silicon–tin alloy sintered from a gas-phase atomized powder. (1st September 2015) - Bernard-Granger, Guillaume; Navone, Christelle; Leforestier, Jean; Boidot, Mathieu; Romanjek, Krunoslav; Carrete, Jesús; Simon, Julia
Abstract: An antimony doped magnesium–silicon–tin alloyed powder, prepared by gas-phase atomization from a melt made of the raw elements, has been sintered by spark plasma sintering to manufacture 60 mm diameter pellets of the Mg2 Si0.5875 Sn0.4 Sb0.0125 material. TEM observations enabled to detect nanometer-sized inclusions (averaged diameter of 7 and 10 nm, depending on the sort, 5.1 × 10 −3 inclusions/nm 2 ) dispersed in the bulk of individual grains constituting the as-sintered polycrystal (grain size around 7 μm). These inclusions (most are enriched in Sn and impoverished in Mg/Si in comparison to the surrounding matrix) are thought to scatter lattice vibrations, leading to a dimensionless-thermoelectrical figure of merit (ZT) around 1.4 at 510 °C. It has also been scrupulously verified that the thermoelectrical properties are robust from one area of a given pellet to another one and from one as-sintered pellet to another one.